IBM Cloud Pak for Data with IBM Spectrum Scale Container Native - Schmidt, Gero; Astigarraga, Tara; Acevedo, Paulina; Miller, JJ; Simpson, Dessa; Stewart, Austen; Tosseth, Todd; Tsingine, Jayson; Godinez, Israel (IBM Redbooks, 2021)
This IBM® Redpaper® publication describes configuration guidelines and best practices when IBM Spectrum® Scale Container Native Storage Access is used as a storage provider for IBM Cloud® Pak for Data on Red Hat OpenShift Container Platform. It also provides the steps to install IBM Db2® and several assemblies within IBM Cloud Pak® for Data, including Watson Knowledge Catalog, Watson Studio, IBM DataStage®, Db2 Warehouse, Watson Machine Learning, Watson OpenScale, Data Virtualization, Data Management Console, and Apache Spark. This IBM Redpaper publication was written for IT architects, IT specialists, developers, and others who are interested in installing IBM Cloud Pak for Data with IBM Spectrum Scale Container Native.